2018
DOI: 10.1016/j.molliq.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Details of charge distribution in stable viral capsid

Abstract: We present the results of Molecular Dynamics simulations of a viral capsid with the aim to analyse ion distribution on the capsid's surface that defines its stability. Two systems were modelled, a stable capsid with neutralising number of ions and an unstable capsid with low number of ions. For the ion distribution analysis the capsid's structure was identical and fixed in both simulations. It was then released for the stability analysis. The ion distribution demonstrated two types of the local regions on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…1.3 times). This is different compared to PCV2, where twofold increase is observed [8]. A small peak at 12.6 nm is formed by the ions located in pores impregnated in the wall or located near the wall at concave regions, while the larger peak at 14.2 nm is made of ions near the convex regions and ions in the solution several water layers away from the surface.…”
Section: Ions Distributionmentioning
confidence: 70%
“…1.3 times). This is different compared to PCV2, where twofold increase is observed [8]. A small peak at 12.6 nm is formed by the ions located in pores impregnated in the wall or located near the wall at concave regions, while the larger peak at 14.2 nm is made of ions near the convex regions and ions in the solution several water layers away from the surface.…”
Section: Ions Distributionmentioning
confidence: 70%
“…Since DNA has negatively charged phosphate groups this looks rather plausible for the negatively charged chloride. It was also found that the concentration of chloride inside the virion exceeded that outside and its outer surface is dominated by the positively charged sodium [63]. Sodium and chloride diffuse inside the capsid through special protein channels more slowly than water does.…”
Section: Different Enzymesmentioning
confidence: 99%
“…Investigating the physicochemical properties of virus capsids may necessitate knowledge of their electronic charge distributions (49) and atomistic modeling (50,51). Charges of various atoms in the capsids of PDB-derived PSFs are treated as ‘point’ charges; however, because atomic charges are distributed throughout neighboring atomic positions, a point charge representation can lead to erroneous charge density calculations.…”
Section: Physical Properties Calculatormentioning
confidence: 99%